If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 2g + -5 Reorder the terms: 11 = -5 + 2g Solving 11 = -5 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 11 + -2g = -5 + 2g + -2g Combine like terms: 2g + -2g = 0 11 + -2g = -5 + 0 11 + -2g = -5 Add '-11' to each side of the equation. 11 + -11 + -2g = -5 + -11 Combine like terms: 11 + -11 = 0 0 + -2g = -5 + -11 -2g = -5 + -11 Combine like terms: -5 + -11 = -16 -2g = -16 Divide each side by '-2'. g = 8 Simplifying g = 8
| 876-4x=14x+19 | | 5-9x=190-44x | | -6w+18=20w | | 7=t-6-3 | | 3(m-3)+7(m+3)=16-4(7-m) | | 2x+3=4(x-1)+3 | | X^2-12x+36(x-6)=27(x-8) | | X+1+x=2+2x-1 | | 6k-3=-15 | | 7(x-4)-3=46 | | 2/5(25z-30)=3/5(12z+16) | | 12-8x=137-43x | | 81xy^3+3x^4=0 | | 122-3x=15x+20 | | 4(2x-8)-2=4(x-4)+6 | | 2x+28=9x-28 | | 3(4x-1)=48 | | 0.4(x-4)=7.2 | | 4xy^4-32xy=0 | | -9(x-4)-3=46 | | 0.5x-0.1(5-x)=2.2 | | 77/121 | | -7-6=7-8x | | -3(2x+1)=21 | | 5(4x-3)=11 | | 4y^3+12y^2+5y=0 | | 23=49-7x | | f(x)=x^3-2x^2+2x-6 | | 20-9w=4(15-1w) | | 11+9lnx=6 | | y+11=19 | | 9p+-5=1 |